COMPARATIVE ANALYSIS OF ANTIQUE FURNITURE WITH REGARD TO THE SCANDINAVIAN DESIGN - Namicev, Petar; Shopova, Emilija (Journal of process management and new technologies, 2018)
The style and design, as an artistic expression of its creators, existed in the ancient period, as evidenced by the numerous representative, authentic and unique works. Confirmation of the connection of styles, and the non existence of a clear border between them, is exactly the connection of the antique furniture to the Scandinavian one. The Scandinavian design, driven by the correlation with nature and the need for durable, simple, functional, yet perfect furniture pieces, finds its connection to the ancient design and its unique historical values. Today’s modern Scandinavian style, as a design of the 20th century, carries numerous antique elements and peculiarities. Based on a detailed analysis of the characteristics of both styles separately and their individual elements, as well as their comparison, we can see the correlation between them and the direction in which they move.